2015
DOI: 10.2298/abs141112031s
|View full text |Cite
|
Sign up to set email alerts
|

Manganese concentration in plants of the protected natural resource, Kosmaj, in Serbia

Abstract: This study was focused on determining the manganese (Mn) concentration in vegetative organs of 10 plant species (8 woody and 2 herbaceous), from four sites in the protected natural resource Kosmaj. The concentration of Mn was analyzed at the beginning of the vegetation period, during a two-year period (2012-2013). The results indicate a wide range of Mn concentrations, depending on site and plant species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Therefore, it is likely that upper and lower limits should be considered only conditionally. For example, Stanković et al [32] showed that concentration of Mn in the leaves of Q. petraea varied over a broad range (434.5-722.0 µg•g -1 ), depending on properties of the growing site. Intriguingly, De Visser [22] observed various foliage concentration of Mn in three Q. robur populations (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is likely that upper and lower limits should be considered only conditionally. For example, Stanković et al [32] showed that concentration of Mn in the leaves of Q. petraea varied over a broad range (434.5-722.0 µg•g -1 ), depending on properties of the growing site. Intriguingly, De Visser [22] observed various foliage concentration of Mn in three Q. robur populations (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…For some microelements, these are the earliest stages of plant growth, for others it is the period of the formation of the reproductive organs and reproduction itself, and for the third period, accumulation of spare substances in corresponding organs. The way we use microelements is of great significance because their effect depends on various factors (Oljača 2014;Stanković et al 2015).…”
Section: The Importance Of Microelements For the Development Of Plantsmentioning
confidence: 99%
“…Develop a method of removing pollutants from all environmental media for the purpose of its sustainability. Among the many issues that arise in the environment, one of the most serious is without a doubt soil degradation and destruction of forest ecosystems (Stanković et al 2008(Stanković et al , 2013(Stanković et al , 2015. Preventing and stopping the degradation or decrease of degraded soil, afforestation is practiced; that is, the use of technologies that can guarantee good success, and with the possibility of a small investment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation